Financial Liberalization and Economic Growth in Nigeria: An Empirical Evidence - Orji, Anthony; Ogbuabor, Jonathan E.; Anthony-Orji, Onyinye I. (International Journal of Economics and Financial Issues, 2015)
The liberalization thesis has generated a lot of debate in theoretical and empirical literature. In this paper we construct an index of financial liberalization from 1981 to 2012 to investigate its impact on economic growth in Nigeria using the McKinnon-Shaw framework. The Ordinary Least Squares Methodology and cointegration analysis are adopted in the study. The result reveals that financial liberalization (FINDEX) and private investment (PINV) have significant positive impact on economic growth in Nigeria. However, real lending rate (LDR) proved to be negatively related to economic growth in Nigeria within the period under review. We therefore conclude that the monetary authorities and policy makers in Nigeria need to support the liberalization process by formulating complementary policies and financial sector reform measures that will help in strengthening the impact of the liberalization process on the economy and also ensure that the benefits of the liberalization exercise is maximized. Keywords: Financial liberalization; Lending Interest Rate; Private Investment; Economic Growth JEL Classifications: B26; D53; E44; F43.